Enhancing interprofessional collaboration in medication management: The roles of nurses, pharmacists, health records, emergency services, and cardiology - Almanna, Mohammad Abdullah; Alanazi, Dhiyaa Manawer; Enazi, Sami Mohammed Al; Alaboush, Khalid Salem; Alaujan, Badour Subhi; Zamzami, Bander Ahmad; Alanazi, Nadin Lafi; Ababtain, Hind Amer; Altalouhi, Fatmah Malfi; Alenizi, Eman Smair; Aldossary, Ghuzyel Fahad; Alowaidan, Salwa Rashed; et al. (International journal of health sciences, 2022)
Background _ Although there is ample data supporting the positive impact of nurse-pharmacist cooperation on clinical health outcomes and cost-effectiveness in increasing drug safety among adults in acute care settings, there is a lack of research in community settings. Aim of Work – The objective is to consolidate information and examine the nurse’s role in medication management during transitional care. Methods – A comprehensive systematic review was done. A systematic search was conducted in electronic databases comprising PubMed (including Medline), Web of Knowledge, Scopus, and Cinahl, covering the period from January 2010 to April 2021. covered in this study were original qualitative and quantitative research papers published in English that specifically examined the nurse’s involvement in managing medications during transitional care. This covered situations when patients moved between short-term, long-term, and community healthcare settings. Results – Through the search method, 10 papers were retrieved. These studies were published in English between the years 2014 and 2021. Their primary emphasis was on the nurse’s involvement in managing patients’ medications throughout transitional care in different healthcare settings. The review results were presented narratively using three categories devised by the authors, due to differences in the objectives and approaches of the chosen research.